Teaching Tawhid through Prophetic Narratives: Exploring Faith Values in Islamic Religious Education Textbooks - Nur Hayati; Satriani; Fina Junita; Nur Naila; NurLini (Postgraduate Program of the State Islamic Institute of Palopo, 2024)
Faith formation constitutes a central objective of Islamic Religious Education, particularly at the elementary school level where students begin to develop their religious understanding and identity. Among the instructional approaches used to transmit Islamic values, prophetic narratives occupy a significant position because they provide concrete examples through which abstract theological concepts can be understood. This study aims to explore the representation of tawhid values in prophetic narratives contained in Islamic Religious Education textbooks and to examine their educational significance for faith formation. Employing a qualitative library research design, the study uses content analysis to investigate narratives of the prophets presented in fourth-grade Islamic Religious Education textbooks. The analysis focuses on identifying and interpreting the representation of three major dimensions of tawhid: tawhid al-rububiyyah, tawhid al-uluhiyyah, and tawhid al-asma’ wa al-sifat. The findings reveal that prophetic narratives function not only as historical accounts but also as pedagogical instruments for transmitting faith values. The stories consistently represent Allah’s sovereignty, exclusive worship of Allah, and belief in Allah’s names and attributes through meaningful narrative experiences that are accessible to young learners. Furthermore, the narratives integrate theological teachings with moral virtues such as patience, honesty, perseverance, responsibility, and trust in Allah, thereby supporting both faith formation and character development. This study contributes to Islamic educational scholarship by repositioning prophetic narratives as pedagogical resources for tawhid education rather than merely moral or historical stories. The findings highlight the strategic role of Islamic Religious Education textbooks in facilitating value internalization, religious socialization, and the development of students’ faith-oriented identities.